Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1432-1033.2003.03970.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing involvement of sulfoquinovosyl diacylglycerol in photosystem II in two species of unicellular cyanobacteria

Abstract: Biochem. 269, 2353Biochem. 269, -2358. To understand the spread of the taxa in which PSII interacts with SQDG, especially in cyanobacteria, we produced a mutant defective in the putative sqdB gene responsible for SQDG synthesis from two cyanobacteria, Synechocystis sp. PCC6803 and Synechococcus sp. PCC7942. The mutant of PCC6803, designated SD1, lacked SQDG synthetic ability and required SQDG supplementation for its growth. After transfer from SQDG-supplemented to SQDG-free conditions, SD1 showed decreased ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 34 publications
1
64
0
Order By: Relevance
“…Whereas DGDG is essential in Synechococcus but not in Synechocystis, the reverse is true for the requirement of SQDG-the other glycolipid in thylakoid membranes. This anionic glycolipid is essential in Synechocystis (Aoki et al, 2004), whereas the genes required for SQDG synthesis can be knocked out in Synechococcus without effect under optimal conditions (Güler et al, 1996(Güler et al, , 2000. The…”
Section: Physiological Functions Of Dgdg In Thylakoid Membranesmentioning
confidence: 99%
“…Whereas DGDG is essential in Synechococcus but not in Synechocystis, the reverse is true for the requirement of SQDG-the other glycolipid in thylakoid membranes. This anionic glycolipid is essential in Synechocystis (Aoki et al, 2004), whereas the genes required for SQDG synthesis can be knocked out in Synechococcus without effect under optimal conditions (Güler et al, 1996(Güler et al, , 2000. The…”
Section: Physiological Functions Of Dgdg In Thylakoid Membranesmentioning
confidence: 99%
“…PCC7942 (Gü ler et al, 1996), Synechocystis sp. PCC6803 (Aoki et al, 2004), Chlamydomonas reinhardtii (Sato et al, 1995), and Arabidopsis (Arabidopsis thaliana; Yu et al, 2002), and roles of SQDG in photosynthesis have been studied with these mutants. An analysis of the mutants indicated that the level of responsibility of SQDG for photosynthesis differed among the organisms.…”
mentioning
confidence: 99%
“…It has been thought that photosynthetic organisms require constant anionic lipid content by keeping a certain total level of PG and SQDG; if necessary, the two anionic lipids could substitute for each other to some extent, such that the photosynthetic apparatus can function properly and normally. It was found that several photosynthetic organisms, depending on available sources of nutrition, could reciprocally adjust the PG and SQDG contents and maintain the level of the sum of these anionic lipids (Benning et al, 1993;Sato et al, 1995;Guler et al, 1996;Essigmann et al, 1998;Yu et al, 2002;Aoki et al, 2004). However, the increased SQDG in this pgpB mutant could not recover its decreased CO 2 -dependent photosynthetic activity and DCBQ-dependent PSII activity, suggesting the different role for PG and SQDG in maintenance of thylakoid properties in Anabaena sp.…”
Section: Parametersmentioning
confidence: 82%
“…However, the increased SQDG in this pgpB mutant could not recover its decreased CO 2 -dependent photosynthetic activity and DCBQ-dependent PSII activity, suggesting the different role for PG and SQDG in maintenance of thylakoid properties in Anabaena sp. PCC7120, as suggested by Aoki et al (2004).…”
Section: Parametersmentioning
confidence: 99%